Interferência do consumo de dieta hiperlipídica nos sinais de alergia alimentar experimental - Ariane Barros Diniz (2015)
Introduction and Objective: Food allergy can be considered a manifestation of exacerbated immune response to antigens that reach the body orally, most of which are mediated by IgE. It has been shown that several nutritional components can affect positively or negatively this response. Using an experimental food allergy model, we have observed a several signals, including a drastic weight loss associated to adipose tissue inflammation. In this work, our objective was investigated the consequences of a high-fat diet in this process. Methods and Results: BALB/c male mice were separated into four experimental groups: SDC (standard diet, not sensitized), SDS (standard diet, sensitized), HFC (high-fat diet, not sensitized) and HFS (high-fat diet, sensitized). After five weeks of each diet, animals were sensitized subcutaneously with ovalbumin (OVA) with Al(OH)3, with a booster (only OVA) two weeks later. One week after the booster, all animals received an oral challenge with OVA, for one week. Non-sensitized animals receiving the HF diet had higher fat index area and adipocytes, increased leptin and adiponectin levels. Sensitized animals independent of diet offered consume less of the OVA solution. The isolated allergy was able to generate changes in intestinal morphology but did not affect glucose, cholesterol and secretory IgA levels. Allergic mice receiving the HF diet showed lower serum anti-ovalbumin IgE levels. The food allergy in conjunction with the HF diet caused an increase of food intake; more weight loss after oral challenge; reduction in levels of serum triglycerides; liver changes, adhesion and rolling of leukocyte in adipose tissue and accumulation of fat in the enterocytes. However, did not affect the total count and differential blood cell and the relationship villus/crypt intestinal. Conclusion: The consumption of high-fat diet has negative impact on food allergy.